1988
DOI: 10.1152/ajpgi.1988.254.5.g748
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic function in the liver after hepatic venous pressure elevation

Abstract: The liver lymphatic system plays an important role in removing excess fluid from the hepatic tissue. A complete analysis of the liver lymphatic system would be difficult. However, we used a simple circuit-analysis technique to represent the intrahepatic portion of the lymph system as a single pressure source (PL) pushing lymph through a single resistance (RL). Liver lymphatic vessels were cannulated in nine halothane-anesthetized dogs. The lymphatic vessel outflow pressure (PO) was varied by raising the outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Within the interstitium, following Elk et al (1988), we assume that lymph uptake follows a linear relationshipwhere is the conductance of the lymphatic vessels and is the pressure within the flowing lymph; negative uptake is not possible, due to the presence of valves. See also the papers by Stewart and Laine (2001) and by Quick et al (2008), and Appendix 6.4.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the interstitium, following Elk et al (1988), we assume that lymph uptake follows a linear relationshipwhere is the conductance of the lymphatic vessels and is the pressure within the flowing lymph; negative uptake is not possible, due to the presence of valves. See also the papers by Stewart and Laine (2001) and by Quick et al (2008), and Appendix 6.4.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Elk et al (1988) performed experiments on anesthetized dogs weighing 20–30 kg to determine the flow rate into the lymphatic vessels as a function of interstitial pressure. They found that the volumetric flux of lymph leaving the liver equaled , where O min/ is the resistance of the ducts.…”
Section: Appendix A: Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They are therefore empirical (descriptive) parameters (15). To date, R L and P p have been used to describe lymphatic function in a number of organs (16,18,20,43,45) but have yet to be assigned particular physiological interpretations. Much like K f , a black box parameter relating hydrostatic and colloid osmotic pressure gradients to microvascular filtration and C, a black box parameter relating interstitial fluid R655 EDEMAGENIC GAIN AJP-Regul Integr Comp Physiol • VOL 294 • FEBRUARY 2008 • www.ajpregu.org volume to pressure, R L and P p are similar black box parameters, which relate lymphatic outflow to interstitial fluid pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Inflation was continued until a stable portal pressure of 17.5 mm Hg was observed. This venous hypertension in both the liver and intestines resulted in increased microvascular pressures, increased microvascular filtration, increased interstitial fluid volume and pressure, and increased lymph flow from both organs (6,7,15). The pressure within the cisterna chyli was monitored until it increased to a stable value.…”
Section: Rh Stewart and Ga Lainementioning
confidence: 99%